If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 130 = -5(3x + -5) Reorder the terms: 130 = -5(-5 + 3x) 130 = (-5 * -5 + 3x * -5) 130 = (25 + -15x) Solving 130 = 25 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 130 + 15x = 25 + -15x + 15x Combine like terms: -15x + 15x = 0 130 + 15x = 25 + 0 130 + 15x = 25 Add '-130' to each side of the equation. 130 + -130 + 15x = 25 + -130 Combine like terms: 130 + -130 = 0 0 + 15x = 25 + -130 15x = 25 + -130 Combine like terms: 25 + -130 = -105 15x = -105 Divide each side by '15'. x = -7 Simplifying x = -7
| 7x+9=49x^2+126x+81 | | 5X+X=6X+3 | | 2x-y+6z=20 | | x+7-2=3x | | 4-6x+8=1-5x-4 | | 8=3h+5 | | (0-k)(1-k)=0 | | 2x^2+10+52=0 | | (X+3)+2(X-4)=5(X+3) | | (0-k)(0-k)=0 | | X+2x+2x-30=140 | | 9(x+8)+12=8(x+18)+10 | | Y=-3x*2 | | Y=4x^2+3x | | 2=2x-6x+3x+9 | | 360-65-x=44 | | q=40+-0.5p | | 3+4(2x+5)=39 | | 48/6= | | x^2+30x-40=0 | | 5x+5=52 | | 4-293x-4=1-(5x+4) | | 0+50*1-60-60*0+10=C | | q=40-0.5p | | -100+82=x | | 4(5x-1)-10x=3 | | -6x-3.4=3x+.2 | | -70-(-58)=x | | x^2+12x+56=0 | | -6x(x+4)-x^2+8-5x= | | 7x^8-38x^6+15x^4=0 | | 5x^4-11x^2+2=0 |